EDUKASI PERSEBARAN COVID-19 DAN KETAHANAN PANGAN PADA KAMPUNG PADAT PENDUDUK DI KOTA SURAKARTA - Djoko Suhardjanto; Samantha Thaidy; Yeni Priatnasari (Jurnal KeDayMas: Kemitraan dan Pemberdayaan Masyarakat)
Abstrak Universitas Sebelas Maret (UNS) through the Institute of Research and Community Service (LPPM) held a Real Work Lecture (KKN) UNS against Covid-19. Students become covid-19 outbreak response volunteers who are expected to help the government provide education about Covid-19 to the public to remain vigilant and implement healthy lifestyles during the Covid-19 pandemic. KKN UNS Covid-19 Phase 2 is held for 45 days, starting from May 15th – June 30th, 2020. The methods used are online and offline socialization and education on the prevention of covid-19 virus spread, the latest information on Covid-19, online learning, and agriculture for food security. Media used are social media such as whatsapp, youtube, and instagram. The result of the activities or programs that have been implemented is that the community realizes the importance of maintaining mental and physical health during the Covid-19 pandemic, the community is ready to face the adaptation of new savagery, providing education about agriculture at home so that food needs are met during the Covid-19 pandemic, people, especially students, can obtain online learning materials.